The Juridical Review of Death Penalty Imposition in Indonesia Seen From a Human Rights Perspective - Neves, Angelo (Law Development Journal, 2022)
Pancasila is the source of all sources of law, including criminal law. The meaning of Pancasila mustanimating the goals of criminal law. In other words, apart from having to reflect Pancasila, criminal purposes must also be implemented with the spirit and soul of Pancasila. Indonesia is one of the countries that consistently enforces capital punishment in its national law amidst the debate over the existence of capital punishment. The pros and cons that always arise regarding the death penalty are nothing but always associated with violations of human rights. The application of capital punishment by the State through a court decision means that the State takes away the convict's right to life which is a human right that cannot be restricted (non-derogable) in nature. Therefore its application must pay attention to the human rights of convicts. The purpose of this study is to determine the death penalty for the perpetrators of crimes, whether or not it conflicts with human rights and the criteria for imposing capital punishment for perpetrators of crimes that do not conflict with human rights. The method used is a normative juridical approach using secondary data. It can be concluded that the imposition of capital punishment is contrary to human rights and the determination can be justified on the basis of defending human rights and only for crimes that are beyond humanity.